Effect of vitrification on morphology and in-vitro maturation outcome of human immature oocytes - Mohsenzadeh, Mehdi; Khalili, Mohammad Ali; Nazari, Saeedeh; Hemayatkhah Jahromi, Vahid; Agharahimi, Azam; Halvaei, Iman (Italian Journal of Anatomy and Embryology, 2012)
Background. In assisted reproductive techniques, 85% retrieved oocytes are mature, and the rest are immature. These immature oocytes may be matured in vitro, and used in subsequent in vitro fertilization program. The purpose of this study was to determine the maturation capacity and morphology of human immature oocytes in both fresh and vitrified-thawed, in vitro matured oocytes with regard to the maternal age and cause of infertility. Materials & Methods. The first group of immature oocytes (n=103) were directly matured in vitro (fIVM), and the second group (n=102) were vitrified and stored in liquid nitrogen. After thawing, the samples underwent in vitro maturation (vIVM). Oocyte maturation was assessed by the presence of the 1st polar body and pronuclei. After 48 h incubation, each matured oocyte was assessed for ooplasm color, periviteline space normality and shape regularity. Results. After retrieval, 27% oocytes were immature (9.5 % metaphase I and 17.5% germinal vesicle stage). The rate of maturation of fIVM (61.2%) was significantly higher than that of vIVM (33.3%). The percentage of maturation in women under age of 30 was higher in both fIVM and vIVM. The maturation rate after IVM was higher in patients with male infertility than in those suffering of ovarian infertility. Conclusion. Vitrification is a suitable technique for preservation of immature oocytes, especially at the germinal vesicle stage, in stimulated ovarian cycles. It should be noted that the maturation outcome of oocytes at germinal vesicle stage was better than that of metaphase I oocytes. Therefore, we recommend vitrifying germinal vesicle stage oocytes for subsequent in vitro maturation.